Per un’altra retorica della φιλοτιμία: voci femminili, uomini politici e discorsi pubblici. Considerazioni sulla presenza dell’etera nell’opera di Platone (Itinera, 2012)
The purpose of my paper is to express effective hypotheses on the character of the hetaira in some of Plato’s dialogues, particularly in the Symposium – where its presence is implicit in the role of Alcibiades as the lover – and in the Menexenus, my starting point to investigate the character of Aspasia, the greatest courtesan of ancient Greece. I will also underline the relation between the courtesan and the sophistic rhetoric. My final remarks will provide some concise analysis of the history of women and of gender studies in Italy.